Market Stability Reserve under exogenous shock: The case of COVID-19 pandemic. (1st February 2021) - Azarova, Valeriya; Mier, Mathias
Abstract: The EU implemented the Market Stability Reserve (MSR) in response to the 2008 financial crisis to deal with short-term impacts of future shocks, such as the COVID-19 pandemic. We link a model that intertemporally optimizes the handling of banked allowances every five years with one that simulates the annual working of the EU ETS including the MSR with its potential cancelling. Neglecting the pandemic, 2.16 billion allowances are cancelled. Accounting for the pandemic, 0.28 billion additional allowances are cancelled if the European economy fully recovers by 2021, which even overcompensates the 2020 drop in CO2 emissions. Additional cancelling increases when the pandemics lasts longer, meaning that the MSR even outperforms its initial purpose. Thus, we conclude that no additional policy measures to support abatement are required in response to the COVID-19 pandemic. Highlights: We analyse impact of COVID-19 pandemic on EU ETS and MSR. MSR passes the test of COVID-19 triggered shock and fulfils its task in regulating supply of allowances. MSR even outperforms its initial purpose of handling only the short-term impact of a shock. No additional policy measures are necessary in response to the COVID-19 induced shock.